Generation of a nitric oxide signaling pathway in mesenchymal stem cells promotes endothelial lineage commitment. Issue 11 (17th April 2019) - Bandara, Nadeeka; Gurusinghe, Saliya; Kong, Anne; Mitchell, Geraldine; Wang, Le‐Xin; Lim, Shiang Y.; Strappe, Padraig
Abstract: Enhancing differentiation of mesenchymal stem cells (MSCs) to endothelial cells may improve their ability to vascularize tissue and promote wound healing. This study describes a novel role for nitric oxide (NO) in reprogramming MSCs towards an endothelial lineage and highlights the role of Wnt signaling and epigenetic modification by NO. Rat MSCs were transduced with lentiviral vectors expressing endothelial nitric oxide synthase (pLV‐ eNOS ) and a mutated caveolin gene (pLV‐ CAV‐1 F92A ) to enhance NO generation resulting in increased in vitro capillary tubule formation and endothelial marker gene expression. An exogenous source of NO could also stimulate CD31 expression in MSCs. NO was associated with an arterial‐specific endothelial gene expression profile of Notch1, Dll4, and Hey2 and significantly reduced expression of venous markers. Wnt signaling associated with NO was evident through increased gene expression of Wnt3a and β‐catenin protein, and expression of the endothelial marker Pecam‐1 could be significantly reduced by treatment with the Wnt signaling inhibitor Dkk‐1. The role of NO as an epigenetic modifier was evident with reduced gene expression of the methyltransferase, DNMT1, and bisulfite sequencing of the endothelial Flt1 promoter region in NO‐producing MSCs showed significant demethylation compared to control cells. Finally, subcutaneous implantation of NO‐producing MSCs seeded in a biomaterial scaffold (NovoSorb®) resulted in survival of transplanted cells and the formation of blood vessels. In summary, this study describes, NO as a potent endothelial programming factor which acts as an epigenetic modifier in MSCs and may provide a novel platform for vascular regenerative therapy. Abstract : Gene modification of mesenchymal stem cells (MSCs) with endothelial nitric oxide synthase and a caveolin mutant results in the generation of endothelial‐like cells. Nitric oxide (NO) produced from MSCs was associated with Wnt signaling and affected epigenetic modification through downregulation of DNMT1. Subcutaneous transplantation of NO‐producing MSCs resulted in neovessel formation.